Use of Balanced Fertilization for achieving higher productivity of Pearl millet and soil health under pearl millet-based cropping systems: Pearl millet balanced fertilization - Meena, Mahesh Chand (Annals of Arid Zone, 2023)
In India, Pearl millet grown in 7.41 million ha area with an average production of 10.3 million tonnes. Analysis of 1030 soil samples from major pearl millet growing areas representing 10 districts indicated widespread multi-nutrient deficiency involving 2 to 6 nutrients including NK, NKS, NKB, NPKS, NKSZn and NPKSZnB. Incidence and expansion of such multi-nutrient deficiencies in Indian soils owing to inadequate and unbalanced nutrient input through fertilizers is considered one of the major constraints in enhancing productivity of pearl millet. In this context, different nutrient supply options were evaluated with pearl milet-based cropping systems. In all these experiments, SSNM proved superior to state recommendation and farmers’ fertilizer practice in terms of annual pearl millet yields, nutrient recovery, soil fertility restoration and net economic returns. Site-specific nutrient management (SSNM) seems to be one of effective ways to improve nutrient supplying capacity of soil and enhance the productivity of pearl millet in India.